Development of Virtual Reality Based Maritime Literature Learning: Exploring Madurese Local Wisdom in the Folklore of Jokotole - Ahmad Jami'ul Amil; Prita Dellia; Nor Hasimah Ismail; Mohammad Syawal Narawi (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study focuses on the development of Virtual Reality (VR)-based language learning media, literature, and teaching to enhance writing skills and facilitate the process of learning literature and local knowledge related to ships, naval warfare strategies, and understanding Jokotole stories while incorporating local wisdom. The research follows the Borg and Gall Research and Development model, consisting of seven stages: problem identification, information gathering, product design, product testing, design revision, design validation, and product revision. The developed learning media is intended for use on android or similar devices, utilizing a virtual box, and integrates Madurese local wisdom from folklore through VR technology. The research aims to address two main questions: (1) How to develop VR-based learning media for maritime literature that focuses on local wisdom related to sailing and naval warfare strategies in Jokotole folklore, and (2) What is the process of reading learning using VR media? The research findings include the development of a storyboard based on the Jokotole legend using unity software and limited to five events. The naval strategy incorporates the influence of the Jokotole figure and their authority. Furthermore, shipping technology and weapons involve the use of sickles, machetes, and whips, while the ship model (Cadik) functions as transportation. The study concludes that the process of learning literature using VR media enhances student enthusiasm and facilitates the formation of writing ideas. VR media is highly engaging for students and can be an alternative approach in literature learning, allowing for the reinterpretation of folklore content.